Young, Muslim and criminal : experiences, identities and pathways into crime (POLICY Press, 2018)
Qasim gained unique first-hand insight into the multifaceted lives of a group of young British male Muslims who offend after spending 4 years studying them. He unwraps their lives, explores their identities and explains what role religion and Pakistani culture play in their criminal behaviour.